Kebijakan Perlindungan Anak Korban Kejahatan Seksual Di Cirebon - Rahman, Nur; Sarip, Sarip (Jurnal Hukum & Pembangunan, 2020)
This research is motivated by the local media in Cirebon since May 2016-2018 cannot be separated from the discussion and data that Cirebon is categorized as an emergency of child violence. The category of emergencies can be known from data on the increase in child violence in 2016 with 30 cases recorded, in 2017 there were 126 cases, and in early 2018 it increased to 147 cases. What is the ideal policy for realizing child protection? What steps should be taken by the regional government in Cirebon in responding to areas that are included in the emergency situation of child victims of sexual crimes? The method used in this study uses a normative juridical method approach, starting from the provisions of the legislation and examined in the field to obtain supporting factors and obstacles. In Cirebon itself sexual violence as reported by the media is still high and requires government policies that favor children. Government policies in Cirebon are very confusing for the people in Cirebon itself, especially regarding violence against children.